Autoimmune comorbidities in Hashimoto's thyroiditis: different patterns of association in adulthood and childhood/adolescence. Issue 2 (February 2017) - Ruggeri, R M; Trimarchi, F; Giuffrida, G; Certo, R; Cama, E; Campennì, A; Alibrandi, A; De Luca, F; Wasniewska, M
Abstract : Objective: Hashimoto's thyroiditis (HT), the most common autoimmune thyroid disease at any age, is often associated with other autoimmune diseases. The present study was aimed to describe the type and frequency of non-thyroidal autoimmune diseases (NTADs) in HT patients and to delineate the clinical pattern of diseases clustering in pediatric/adolescent and adult age. Design: Cross-sectional study. Methods: 1053 newly diagnosed HT patients (500 adults (467 F, mean age 40.2 ± 13.7 years) and 553 children/adolescents (449 F, mean age 11.1 ± 3.0 years)) were evaluated for common NTADs by means of careful recording of medical history, physical examination and assessment of selected autoantibody profiles. Results: The prevalence of associated NTADs was significantly higher in adults than that in pediatric/adolescent HT patients ( P < .0001). In addition, the number of adult patients suffering from two or more associated NTADs was significantly higher than that of children/adolescent ( P < 0.0001). A female prevalence was evident in both cohorts, but was significant in the adults ( P < 0.0001). The epidemiological distribution of NTADs was strongly different in the two cohorts, the most frequent associated diseases being arthropathies and connective tissue diseases in adults and type 1 diabetes and coeliac disease in children/adolescents. Skin diseases were represented with similar prevalence in both cohorts, vitiligo being the most common. Conclusions: Age at HT presentation may influence autoimmune diseases clustering, favoring the association of specific NTADs in different ages of life. Moreover, the association between HT and NTADs increases with age and occurs most frequently in adults.